STATE OF SCIENTIFIC DEVELOPMENT OF PROBLEMS OF CRIMINAL PROCEDURAL EVIDENCE (Bulletin of criminological association of Ukraine, 2024)
The article emphasizes the analysis of the current state of development of scientific ideas about evidence in the criminal process. The existence of two key areas of research on the problems of evidence in criminal proceedings under the legal regime of martial law is emphasized. The first area covers the theoretical principles of evidence in the criminal process of Ukraine, which are of fundamental importance for the formation of concepts of evidence under martial law. The second area focuses on the procedural and forensic aspects of evidence, analyzing the features of its implementation in such specific conditions, as well as studying the problems of evidence regarding certain types of crimes characteristic of the period of the legal regime of martial law. Based on the above, it is concluded that the scientific results in these areas are in a dialectical relationship, where the theoretical basis becomes the basis for solving applied problems. It is emphasized that the level of research on the issue of proof under martial law remains insufficient, since existing works are fragmentary and do not provide a comprehensive coverage of the problem. In view of this, it is noted that there is an urgent need for a comprehensive study of both theoretical and practical aspects of this issue, which will allow for effective solutions in the fields of science and law enforcement.
Keywords: proof; evidence; criminal proceedings; criminal justice; criminal procedural legislation; judicial practice; state of development